Sofia intermediate catheter and the SNAKE technique: safety and efficacy of the Sofia catheter without guidewire or microcatheter construct. (2nd August 2017) - Heit, Jeremy J; Wong, Johnny HY; Mofaff, Adrienne M; Telischak, Nicholas A; Dodd, Robert L; Marks, Michael P; Do, Huy M
Abstract : Background: Neurointerventional surgeries (NIS) benefit from supportive endovascular constructs. Sofia is a soft-tipped, flexible, braided single lumen intermediate catheter designed for NIS. Sofia advancement from the cervical to the intracranial circulation without a luminal guidewire or microcatheter construct has not been described. Objective: To evaluate the efficacy and safety of the new Sofia Non-wire Advancement techniKE (SNAKE) for advancement of the Sofia into the cerebral circulation. Methods: Consecutive patients who underwent NIS using Sofia were identified. Patient information, SNAKE use, and patient outcome were determined from electronic medical records. Sofia advancement to the cavernous internal carotid artery or the V2/V3 segment junction of the vertebral artery was the primary outcome measure. Secondary outcomes included arterial vasospasm and arterial dissection. Results: 263 Patients (181 females, 69%) who underwent a total of 305 NIS using Sofia were identified. SNAKE (SNAKE+) was used in 187 procedures (61%). Two hundred and ninety-three procedures (96%) were technically successful, which included 184 SNAKE+ NIS and 109 SNAKE− NIS. Primary outcome was achieved in all SNAKE+ procedures, but not in five SNAKE− procedures (2%). No arterial dissections were identified among 305 interventions. In the intracranial circulation, a single SNAKE+ patient (0.5%) had non-flow limiting arterial vasospasm involving the petrous internal carotid. Three SNAKE+ patients (1.6%) and one SNAKE− patient (0.8%) demonstrated external carotid artery branch artery vasospasm during dural arteriovenous fistula or facial arteriovenous malformation treatment. Conclusion: SNAKE is a safe and effective technique for Sofia advancement. Sofia is a highly effective and safe intermediate catheter for a variety of NIS.